Industrial fishing and its impacts on food security: a systematic review - Farquhar, Samantha D.; Heck, Nadine; Maps, Frédéric; Wade, Eric; Asch, Rebecca G.; Cenek, Martin; Kirchoff, Jon F. (Frontiers in Ocean Sustainability, 2024)
This systematic review seeks to answer the question: how have previous studies conceptualized and measured food security in relation to industrial fisheriesindustrial fishing? Following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) methodology, initial searches yielded 983 publications, which were distilled to 55 relevant articles for in-depth analysis after the screening process. These studies span from 1997 to 2024, covering a diverse range of geographical contexts, and cover a variety of scales from local community impacts to national and global trends. Overall, four principal themes related to the perceived positive and negative and direct and indirect impacts of industrial fishing on food security were identified: 1) Industrial fishing activities provide jobs to local populations of which earnings are used to purchase other food items; 2) Industrial fishing activities provide fisheries products to local markets which are used as a common food source; 3) Industrial fishing activities damage the environment, leading to a decrease in the availability of catch for food or livelihood; 4) Industrial fishing activities outcompete local users and export catch to distant markets, thereby decreasing available food to local communities. A notable gap in the research is the lack of integration of complex data on industrial fishing, such as detailed catch records and fishing efforts, with the multifaceted aspects of food security, including detailed household consumption trends. This separation has often led to studies focusing on either fishing activities or food security outcomes in isolation, which can oversimplify the relationship between fisheries production and food security. The findings highlight the need for a more integrated research approach that combines fisheries or ecosystem data with a thorough examination of household consumption behaviors and broader food systems. Such an approach is critical for devising effective policies and interventions that sustain and enhance the livelihoods of communities dependent on fisheries.